2003
DOI: 10.1007/s00216-003-1905-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure of silica in Equisetum arvense

Abstract: Silicified regions in the stem and leaf of the horsetail Equisetum arvensewere studied by scanning and transmission electron microscopy. The silica was present as a thin layer on the outer surface with variation in the size of this layer depending on the part investigated. There was a dense arrangement of silica spheres with some density fluctuations. A loose arrangement of silica particles with variation in their size was found beneath this dense arrangement suggesting the agglomeration of silica. An electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 18 publications
3
35
0
7
Order By: Relevance
“…Additionally, such conditions were not reproducible in the simulation despite the lower abrasion rate in the tumbler. Stomach juices and hard plant matter, including silica-rich material such as horsetail (Holzhçter et al 2003), did certainly not play the key role in polish formation of sauropodomorph gastroliths.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, such conditions were not reproducible in the simulation despite the lower abrasion rate in the tumbler. Stomach juices and hard plant matter, including silica-rich material such as horsetail (Holzhçter et al 2003), did certainly not play the key role in polish formation of sauropodomorph gastroliths.…”
Section: Discussionmentioning
confidence: 98%
“…Elle est particulièrement indiquée pour une cure reminéralisante, d'autant plus que la silice a une action directe sur les cellules osseuses, ou ostéoblastes [37].…”
Section: Prêle (Equisetum Arvense)unclassified
“…It has been shown that the silicification of cells, such as Bdumb-bell-shaped cells^in silica cells, vascular bundles, and silica bodies of bulliform cells, is not restricted to the leaf blades of rice because silicified cells may be found inside the epidermal layer as well as in the vascular tissues of the stem, hull, and leaf sheath (Prychid et al 2003). Another study on Equisetum indicated that the silicified structures can be found on the epidermal surface of the cell wall (Holzhüter et al 2003). The silicified cells produced in the different tissues including vascular tissue, leaf blade, epidermis stem, hull, and leaf sheath cooperate to protect against a wide range of stresses in plants (Hodson et al 2005).…”
Section: Silicon Absorption and Transportationmentioning
confidence: 97%